A comparative study on the governance approaches for biotechnological risks - Wang, Yuexin (Frontiers in Bioengineering and Biotechnology, 2025)
The governance approaches for biotechnological risks mainly include the laissez-faire approach, which emphasizes “technology first” but suffers from lagging governance; the preventive approach, which emphasizes “safety first” and uses quantitative risk-benefit analysis as the main method in a single dimension; and the precautionary approach, which also emphasizes “safety first” but has three dimensions of cognition, procedure, and action, and is characterized by forward-looking and proportionality. Emerging biotechnologies are developing rapidly while being filled with a large amount of uncertainty, which increases the complexity of potential biotechnological risks. The precautionary approach, which emphasizes cultivating a cautious awareness and future responsibility in cognition, reversing the burden of proof in procedure, and ensuring that the level of precautionary measures is proportionate to the level of risk in action, is conducive to dealing with various risks including uncertainty risks and meets the needs of biotechnological risks governance, providing a strong theoretical guarantee for the balance between technological progress and social security development.